Examination of industrial robot performance parameters utilizing machine tool diagnostic methods. (13th February 2020) - Kuric, Ivan; Tlach, Vladimír; Císar, Miroslav; Ságová, Zuzana; Zajačko, Ivan
The article discusses the possibility to identify changes in robot accuracy based on deformation of the circular path measured by the Renishaw Ballbar system. The research method utilizes correlation between industrial robot accuracy and precision of method used for the so-called calibration process. The presented experiments consist of two basic parts. The first is positional analysis with a simulation model of the robot in Creo Parametric 4.0. The second part describe practical measurements using the Renishaw Ballbar QC20-W and the Renishaw XL-80 laser interferometer. The results of the experiments confirm that Renishaw Ballbar can be used to quickly and simply identify occurrence of changes in the condition of an industrial robot.